Antimicrobial Resistance, Virulence Genes, and Biofilm Formation Capacity Among Enterococcus species From Yaks in Aba Tibetan Autonomous Prefecture, China - Cui, Pengfei (Front Microbiol, 2020)
Yaks provide necessities such as meat and milk for Tibetans living at high altitudes on and around the Qinghai-Tibetan Plateau. Enterococci are ubiquitous members of the animal gut microbiota that can cause biofilm-associated opportunistic infections. Meanwhile, multidrug-resistant Enterococcus also poses a serious threat to public health. This study aims to characterize antibiotic resistance, virulence genes, and biofilm formation of enterococci from yaks. From April 2018 to July 2019, we collected 395 fecal samples of yaks in Aba Tibetan Autonomous Prefecture, China. Enterococci isolated from the samples were identified and classified according to the 16S rDNA sequence. The antibiotic resistance of each isolate was detected according to the Kirby-Bauer disk diffusion method, and antibiotic resistance genes were detected by polymerase chain reaction (PCR) and sequencing. Enterococcal biofilms were assessed using standard procedures. Different virulence genes were detected by PCR and sequencing. In total, 381 enterococci strains were recovered, with Enterococcus faecalis (41.99%) and Enterococcus faecium (37.80%) being the predominant species. Many isolates were multidrug- resistant (60.37%) and showed a high resistance rate to rifampicin (64.30%) and tetracycline (61.54%). We also detected various antimicrobial resistance (AMR) genes in the tested strains. The E. faecalis strains had higher frequency of biofilm formation and virulence genes than other enterococcal species. This is the first report that shows yaks are repositories for drug-resistant enterococci with virulent determinants and biofilms that may spread into humans and to environment. This study also provides useful data suggesting that enterococci may pose a potential health risk to yaks. Therefore, active surveillance of AMR and pathogenesis in enterococci from yaks is urgently warranted.